Influence of Reinforcing Efficiency of Clay on the Mechanical Properties of Poly(butylene terephthalate) Nanocomposite - Maria A. S. Colombo; Francisco R. V. Díaz; Deepa Kodali; Vijaya Rangari; Olgun Güven; Esperidiana A. B. Moura (Ceramics, 2023)
In contrast to traditional fillers, clay, in particular, natural smectite clay, represents an environmentally significant alternative to improve the properties of polymers. Compared to conventional nanofillers, smectite clay can effectively enhance the physical and mechanical properties of polymer nanocomposites with a relatively small amount of addition (<5 wt%). The present study focuses on investigating the reinforcing efficiency of different amounts (up to 5 wt%) of a natural Brazilian smectite clay modified (MBClay) on the mechanical properties of poly(butylene terephthalate) (PBT) nanocomposites and also evaluates the correlation between MBClay addition and the mechanical and thermal behaviors of the PBT/MBClay nanocomposites. Natural Brazilian clay modified by the addition of quaternary salt and sodium carbonate (MBClay) was infused into the PBT polymer by melt extrusion using a twin-screw extruder. It was found that the best properties for PBT were obtained at 3.7 wt% of modified BClay. Tensile strength at break exhibited increased by about 60%, flexural strength increased by 24%, and flexural modulus increased by 17%. In addition, an increase in the crystallinity percentage of PBT/BClay nanocomposite was confirmed by DSC and XRD analysis, and a gain of about 45% in HDT was successfully achieved due to the incorporation of 3.7 wt% of MBClay.